Levamisole Suppresses CD4+ T-Cell Proliferation and Antigen-Presenting Cell Activation in Aplastic Anemia by Regulating the JAK/STAT and TLR Signaling Pathways - Wang, Jiali; Liu, Jia; Wang, Mingyang; Zhao, Fei; Ge, Meili; Liu, Li; Jiang, Erlie; Feng, Sizhou; Han, Mingzhe; Pei, Xiaolei; Zheng, Yizhou (Frontiers in Immunology, 2022)
Aplastic anemia (AA) is a life-threatening disease primarily caused by a metabolic disorder and an altered immune response in the bone marrow (BM) microenvironment, where cytotoxic immune cells attack resident cells and lead to hematopoietic failure. We previously reported an efficient strategy by applying cyclosporin (CSA) combined with levamisole (CSA+LMS based regimen) in the treatment of AA, but the immunoregulatory mechanism of LMS was still unclear. Here the therapeutic effects of LMS were examined in vivo using the BM failure murine model. Meanwhile, the proportion and related function of T cells were measured by flow cytometry in vivo and in vitro. The involved signaling pathways were screened by RNA-seq and virtual binding analysis, which were furtherly verified by interference experiments using the specific antagonists on the targeting cells by RT-PCR in vitro. In this study, the CSA+LMS based regimen showed a superior immune suppressive response and higher recession rate than standard CSA therapy in the clinical retrospective study. LMS improved pancytopenia and extended the survival in an immune-mediated bone marrow failure murine model by suppressing effector T cells and promoting regulatory T cells expansion, which were also confirmed by in vitro experiments. By screening of binding targets, we found JAK1/2 and TLR7 showed the highest docking score as LMS targeting molecules. In terms of the underlying molecular mechanisms, LMS could inhibit JAK/STAT and TLR7 signaling activity and downstream involved molecules. In summary, LMS treatment could inhibit T cells activation and downregulate related molecules by JAK/STAT and TLR signaling pathway, supporting the valuable clinical utility of LMS in the treatment of AA.